Complete Genome Sequences of Six Copper-Resistant Xanthomonas citri pv. citri Strains Causing Asiatic Citrus Canker, Obtained Using Long-Read Technology - Richard, Damien (2017)
The gammaproteobacterium Xanthomonas citri pv. citri causes Asiatic citrus canker. Pathotype A strains have a broad host range, which includes most commercial citrus species, and they cause important economic losses worldwide. Control often relies on frequent copper sprays. We present here the complete genomes of six X. citri pv. citri copper-resistant strains.